Artificial factor VIII deficient plasma: preparation using monoclonal antibodies and its use in one stage coagulation assays. Issue 5 (May 1988) - Hornsey, V S; Waterston, Y G; Prowse, C V
Abstract : Monoclonal antibodies to factor VIII antigen (VIII:Ag) and von Willebrand factor (vWf:Ag) were immobilised on Sephacryl S-1000 and tested for their ability to deplete normal human citrated plasma of factor VIII. A combination of two antibodies to VIII:Ag and one antibody to vWf:Ag was required to produce plasma containing less than 0.01 IU/ml. Its performance in the one stage coagulation assay of VIII:C was equivalent to that of congenital VIII deficient plasma for the assay of normal and haemophilic plasma and factor VIII concentrates. Storage of freeze dried aliquots of this product at -20 degrees C, +4 degrees C, and 37 degrees C showed that it could be used as a substrate for at least six months when stored at temperatures +4 degrees C and below.